PENERAPAN INOVASI TEKNOLOGI PROSES PENGERINGAN JAGUNG BAGI PETANI JAGUNG GUNUNG GEULIS KABUPATEN SUMEDANG - Hidayat, Yayat; Ruswandi, Dedi; Rumidatul, Alfi (LP2M STP Mataram, 2024)
The primary issue confronting maize farmers in Mount Geulis, Sumedang Regency, is the challenge of drying corn and the insufficient understanding of maize drying technologies. The inadequate drying process is compromising the quality of pipil corn and reducing market prices, resulting in substantial losses for farmers. Community service initiatives should be implemented to assist corn farmers in Mount Geulis with the corn drying process and to establish a corn drying facility utilizing turbine ventilator and air kiln dryer (TV AKD) technology. We will accomplish this via a number of community service initiatives, encompassing surveys and social interactions, the design and construction of a greenhouse dryer, training on maize drying methodologies utilizing TV AKD technology, and monitoring and evaluation. Establishing greenhouse TV AKD drier facilities will alleviate the challenges farmers encounter in the corn drying process and enhance their understanding of corn drying technologies